Enhanced hydrogen production from thermochemical processes - Ji, Guozhao; Yao, Joseph G.; Clough, Peter T.; Diniz da Costa, João C.; Anthony, Edward J.; Fennell, Paul S.; Wang, Wei; Zhao, Ming (Royal Society of Chemistry, 2018)
To alleviate the pressing problem of greenhouse gas emissions, the development and deployment of sustainable energy technologies is necessary. One potentially viable approach for replacing fossil fuels is the development of a H2 economy. Not only can H2 be used to produce heat and electricity, it is also utilised in ammonia synthesis and hydrocracking. H2 is traditionally generated from thermochemical processes such as steam reforming of hydrocarbons and the water-gas-shift (WGS) reaction. However, these processes suffer from low H2 yields owing to their reversible nature. Removing H2 with membranes and/or extracting CO2 with solid sorbents in situ can overcome these issues by shifting the component equilibrium towards enhanced H2 production via Le Chatelier's principle. This can potentially result in reduced energy consumption, smaller reactor sizes and, therefore, lower capital costs. In light of this, a significant amount of work has been conducted over the past few decades to refine these processes through the development of novel materials and complex models. Here, we critically review the most recent developments in these studies, identify possible research gaps, and offer recommendations for future research.